Analysis of Physico-Chemical and Bacteriological Parameters of Liquid Effluents from the Provincial Hospital Center in Sidi Kacem Morocco - Elouakfaoui Aziz; Mahjoub Aouane; Rouani Abdeljabbar; Berrid nabyl (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The effluents generated by the hospital activities and which are rejected into themunicipal sewerage system without any prior treatment, present a chemical, biological and physicalrisk for public and environmental health. They cause a degradation of the aquatic ecosystem, and favorthe propagation of antibiotic resistant germs. Objective: The aim of this study is to carry out physicochemicaland bacteriological analysis of the effluents of the provincial hospital of Sidi Kacem in Rabat-Salé-Kénitra region, Morocco, in order to evaluate the degree of wastewater pollution and to reduce itsenvironmental impact.Methods: 24 samples of wastewater were collected from the Hospital’s main sewer according toMoroccan Norm NM 03.7.059 and transported to the Provincial Laboratory of Epidemiology andEnvironmental Health (LPEHM) for analysis. These analyses were conducted according to therequirements and methods recommended by Rodier 1996 and 2009.Results: The results of the bacteriological analysis showed a very high bacterial load of fecal coliforms(36,7.104 CFU/100 ml), total coliforms (40.104 CFU/100 ml), and fecal streptococci (21.104 CFU/100ml). The physicochemical parameters revealed a significant load of organic and mineral matter expressedin terms of nitrates (41,59 mg/l), nitrites (0,53 mg/l), sulphates (222,75 mg/l), ammonia (1,95 mg/l),electrical conductivity (3202 μs/cm), hydrogen potential PH (7.82), all of which are well above theupper limit stipulated by the regulations. The COD/BOD5 ratio (7.66) higher than 3 means that theseeffluents are hardly biodegradable.Conclusion: These results show that hospital effluent is loaded with mineral, organic and bacteriologicalpollutants and requires